25.5k views
5 votes
the ratio of the point (-3,k) divides the line segment joining the points (-5,-4) and (-2,3) also find the value of k

User Ramps
by
6.2k points

2 Answers

0 votes
Step by step equation
User Ynhockey
by
5.7k points
6 votes

Answer:

Explanation:

midpoint theorem : (mx₂+nx₁/m+n , my₂+ny₁/m+n)

(-3, k) = ( -3*-2 + k*-5/-3+k , -3*3 + k*-4/-3+k)

(-3, k) = (6-5k/-3+k , -9-4k/-3+k)

Compare x values of both side ;

-3 = 6-5k/-3+k

-3 *( -3+k) = 6-5k

-3*-3 +k *-3 = 6-5k

9 -3k = 6- 5k

5k -3k = 6 - 9

2k = -3

k= -3/2

User Manjunath Reddy
by
5.5k points